Antenas de microfita sobre substrato dielétrico organizado de forma quase periódica - Medeiros, Thiago Eslley de Lima (Universidade Federal Rural do Semi-Árido, 2013)
The microstrip antennas are in constant evidence in current research due to its numerous advantages. Fractal geometry proposed by Mandelbrot(1975 ) combined with the performance and convenience of planar structures are an excellent combination used in the design of antennas in order to reduce the dimensions and enhance its bandwidth, and allows the emergence of best bands frequency by virtue of ownership of high -similarity. Compared with the conventional microstrip antennas, patch antennas with fractal type substrates have lower resonance frequency, enabling the manufacture of even more compact antennas. The aim of this work consists of the design of patch antennas with dielectric substrates organized almost periodic basis through the use of fractal geometry sequence Cantor applied to a circular patch antenna fed by microstrip line, designed for a resonant frequency of 10 GHz. Analysis of this microstrip antenna is made in various types of dielectric substrates by simulation through software commercial Ansoft HFSS - Designer, used for accurate analysis of the electromagnetic behavior of the antennas by the finite element method by presenting results from resonant frequency and radiation pattern, making comparisons with other results in the literature. This dissertation also presents a bibliographic study on theories of antennas while also addressing about fractal geometry, emphasizing its characteristics and properties as well as its applicability. This paper also presents a study of almost periodic structures and their mathematical formalism considered throughout this work
Keywords: Antenas de Microfita; Fractais; Estruturas quase peródicas; Sequência de Cantor; Microstrip antennas; Fractals; Almost periodic structures; Sequence Cantor; ENGENHARIAS::ENGENHARIA ELETRICA